Autonomous Mental Development at the Individual and Collective Levels: Concept and Challenges - Marco Lippi; Stefano Mariani; Matteo Martinelli; Franco Zambonelli (IEEE Access)
The increasing complexity and unpredictability of many ICT scenarios let us envision that future systems will have to dynamically learn how to act and adapt to face evolving situations with little or no a priori knowledge, both at the level of individual components and at the collective level. In other words, such systems should become able to autonomously (i.e., self-) develop mental models of themselves and of their environment. Autonomous mental development includes: learning models of own capabilities; learning how to act purposefully towards the achievement of specific goals; and learning how to act in the presence of others, i.e., at the collective level. In this paper, we introduce a conceptual framework for autonomous mental development in ICT systems – at both the individual and collective levels – by framing its key concepts and illustrating suitable application domains. Then, we overview the many research areas that are contributing or can potentially contribute to the realization of the framework, and identify some key research challenges.